The Effectiveness of Self-Management Book in Patients with Diabetes Mellitus - Rapitos Sidiq; Widdefrita Widdefrita; Evi Maria Silaban; Nindy Audia Nadira; Marni Handayani; Heny Indriati Lubis (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Diabetes mellitus (DM) is a non-communicable disease that causes complex health problems globally and nationally. In addition to high prevalence and mortality rates, it has an adverse socio-economic impact. To reduce the adverse impacts of diabetes mellitus on the quality of a patient's life, education on self-management is required. This study aimed to determine the effectiveness of self-management books for people with diabetes in improving their self-management.Method: The research was quantitative, with a quasi-experimental design. The samples were people with diabetes mellitus who never received health education or were not respondents to the chronic/PROLANIS disease service program. The total number of samples was 312 people. Data were collected using guided interviews before the intervention from June 26, 2022, to July 10, 2022, and after the intervention from July 28, 2022, to October 27, 2022. Data were processed through editing, coding, transferring, and tabulating. They were analyzed by univariate and bivariate analysis using a paired t-test, with a 95% confidence degree (α = 0.05). They were descriptively presented in tables. Results: The average value of self-management before and after the intervention was 46.37 and 50.42, respectively. The paired t-test showed a p-value of <0.05 (0.001 < 0.05).  Based on the results, a self-management book was effective in increasing the self-management of people with diabetes. In the future, it is necessary to carry out further research to determine the impact of using this book on improving the quality of life of DM sufferers, especially its impact on the stability of blood sugar in DM sufferers.